Enhanced sustainability at the bitumen-aggregate interface using organosilane coating technology. (12th December 2022) - Aldagari, Sand; Hung, Albert M.; Shariati, Saba; Faisal Kabir, S.K.; Ranka, Mikhil; Bird, Richard C.; Fini, Elham H.
Graphical abstract: Highlights: Optimum dosage of organosilane modifier enhances resistance to moisture at the bitumen-aggregate interface. Optimum organosilane-modified bitumen has low susceptibility to thermal and oxidative degradation. Optimum organosilane-modified bitumen shows notable hydrothermal stability. Using an amount of organosilane greater than optimum value increased bitumen's susceptibility to moisture damage. Thick layers of organosilane on stone aggregate are unstable when exposed to hydrolytic treatment. Abstract: This paper uses molecular modeling and laboratory experiments to investigate the merits of an organosilane modifier to enhance resistance to moisture at the bitumen-aggregate interface. The organosilane modifier (referred to as OS1 in this study) forms a coating layer on stone aggregates, bridging between the aggregates and the bitumen molecules. Measurements of the moisture–induced shear-thinning index found the best moisture resistance for a sample with an optimum dosage of 0.6 % OS1 cured at 150 °C for 60 min. The performance of the bitumen modified by the optimum dosage of OS1 was not reduced after being exposed to short-term aging and long-term aging, indicating low susceptibility to thermal and oxidative degradation. For glass beads with the optimum OS1 coating, contact-angle measurements showed notable hydrothermal stability after hydrolysis. However, using an amount of OS1 greater than 0.6 % increased bitumen's susceptibility to moisture damage; thick layers of OS1 were unstable when exposed to hydrolytic treatment. Molecular modeling showed excess OS1 forming thick multiple layers on the silicate substrates; these layers had poor bonding to the first adsorbed OS1 layer, allowing water infiltration into the system. Surprisingly, dry surface adhesion (to bitumen) of an OS1-coated glass bead was nominally less than that of UV–ozone-cleaned glass. The study outcomes highlight the importance of optimizing factors to maximize the effectiveness of a modifier in bituminous composites.